(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to determine the impact of product innovation on the competency level of the fast-food chain in Quezon City in terms of age, gender, educational attainment, civil status, product innovation, process innovation, paradigm innovation, and position innovation. The result of the study reveals that most respondents are females between the ages of fewer than 25 years old. The impact of product innovation on the competency level of fast-food chains in terms of product innovation is that new varieties of products attract customers, and the preference of the consumer and expectation in service and goods is "Agreed." The impact of product innovation on the competency level of the fast-food chain in terms of process innovation. The new product that is highly recommended to other customers is a "Agree." The impact of product innovation on the competency level of the fast-food chains in terms of paradigm innovation using delivery services makes it easier to purchase recently launched goods. The impact of product innovation on the competency level of the fast-food chains in terms of position innovation and the variety of products helps to increase the company’s income. The impact of product innovation on the competency level of the fast-food chains in terms of position innovation and the variety of products helps to increase the company’s income. The problems encountered by respondents in product innovation at the competency level are financial capacity, marketing strategy, cost and budget management, customer service, pricing strategy, product consistency, health and hygiene, and employee training. Overall, the researchers recommend improving dealing with consumer and employee complaints and concerns; employees must have better training for quality service and fast and efficient service that consumes the time of customers to increase the demand.